Understanding Australia’s groundwater spatio-temporal variability in relation to its hydroclimate-hydrogeology - Hu, Kexiang (Curtin University, 2022)
Groundwater is a highly dependent water resource in Australia, yet it is not well understood, leading to different issues from one region to another. Currently, there are four major concerns about Australia’s groundwater; (i) groundwater decline, (ii) necessity of groundwater for agricultural expansion, (iii) data deficiency, and (iv), unclear groundwater recharge threshold conditions. To address these concerns, this thesis, therefore, aims to understand Australia’s spatio-temporal groundwater variation from a hydroclimatic and hydrogeological perspective.